2023
DOI: 10.3390/pr11082366
|View full text |Cite
|
Sign up to set email alerts
|

Modified Model and Simulation Verification of Rock-Fatigue Damage Considering Repeated Discharge Impact

Abstract: The existing rock-fatigue-damage constitutive model fails to consider the influence of discharge energy and discharge times on the effect of rock damage under discharge impact. In this regard, the impact load test of sandstone was carried out. Based on the test results, the quantitative characterization formula of different discharge parameters on the weakening degree of rock compressive strength was established. Based on the TCK (Taylor–Chen–Kuszmaul) model, a constitutive model considering the mechanical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…In the research field of rock fatigue characteristics, it has been found that factors such as loading frequency, temperature, stress amplitude, and cycle number in cyclic loading and unloading tests mainly affect the strength of rock mass [3][4][5]. With more in-depth research, many scholars have become concerned about fatigue damage [6][7][8] and the energy dissipation mechanism [9][10][11] of rock during cyclic loading. Sun et al [12] deduced a damage variable according to the strength characteristics and energy evolution law in the cyclic loading process.…”
Section: Introductionmentioning
confidence: 99%
“…In the research field of rock fatigue characteristics, it has been found that factors such as loading frequency, temperature, stress amplitude, and cycle number in cyclic loading and unloading tests mainly affect the strength of rock mass [3][4][5]. With more in-depth research, many scholars have become concerned about fatigue damage [6][7][8] and the energy dissipation mechanism [9][10][11] of rock during cyclic loading. Sun et al [12] deduced a damage variable according to the strength characteristics and energy evolution law in the cyclic loading process.…”
Section: Introductionmentioning
confidence: 99%